HUKUM EKONOMI TERKAIT PEMBANGUNAN EKONOMI INDUSTRI PERTAHANAN DI INDONESIA - Tri Susdarwono, Endro (Penerbit CV Tentrem Karya Nusa, 2019)
Abstract: Various studies of legal and economic relations show that economic progress will notsuccees without the development of the law that preceded it. In fact it is said that strengtheninglegal institutions is ?precondition for economic change?, ?crucial to the viability of new politicalsystems?, and ?an agent of social change. One of the defense industry management devices deemednecessary to encourage the national industry to become more professional, innovative, effectiveand efficient, integrated in meeting the availability of defense equipment independently, is aregulation number 16 of 2012 concerning the Defense Industry.Key Words: economic law, development, defense industry economic